Pediatric chronic kidney disease mortality in Brazil-A time trend analysis. - Arnauld Kaufman; André L Barreira; Marcelo G P Land (Public Library of Science (PLoS), 2024)
Chronic kidney disease (CKD) is defined based on structural or functional abnormalities of the kidneys, or a glomerular filtration rate (GFR) below the threshold of 60 ml/min per 1.73 m2 for more than 3 months. It is an important noncommunicable disease with a rising worldwide, becoming a global public health problem. There are few studies about this problem, especially in low- and middle-income countries (LMIC), including Brazil, an upper-middle-income country. The objective of the study was to determine the cause-specific mortality rates for pediatric CKD patients (CKDMR) from 0 to 19 years old, based on the 10th revision of the International Classification of Diseases (ICD-10) and the Global Burden of Diseases Injuries and Risk Factors Study's (GBD) list. We calculated the impact of the annual human development indexes (HDI) in CKDMR in Brazil and its regions at two different times and compared it with the literature results. We obtained data from the Department of Informatics of the Brazilian Unified Health System (DATASUS) from 1996 to 2017. The Joinpoint regression analyses estimated the average annual percentage changes (AAPCs). The correlation between the HDI values and the number of deaths from each age group in Brazil and its different regions were assessed using the time series autoregressive integrated moving average (ARIMA) models. There were 8838 deaths in a pediatric and adolescent population of about 1.485 x 109 person-years observed in Brazil from 1996 to 2017. Our results demonstrated a significant increase in the AAPC in Brazil's less than 1-year-old age group and a decrease in children from 5 to 19 years old. We observed a positive correlation between CKDMR and HDI among children under 1 year of age. Conversely, there is a negative association in the age groups ranging from 5 to 19 years, indicating an inverse relationship between CKDMR and HDI.